2017
DOI: 10.1080/13554794.2017.1319958
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain stimulation of the anterior limb of the internal capsule for treatment of therapy-refractory obsessive compulsive disorder (OCD): a case study highlighting neurocognitive and psychiatric changes

Abstract: Obsessive compulsive disorder (OCD) is an anxiety disorder characterized by repeated, unwanted thoughts and behaviors. Individuals with this condition often experience significant emotional distress secondary to their symptoms. Additionally, impairments in attention/concentration, processing speed, and executive functions are typically observed. The exact pathology of OCD remains unknown; consequently, it can be difficult to treat patients with severe symptomatology. Deep brain stimulation (DBS) may be a viabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…ALIC DBS responses appeared to rely on programming adjustments, particularly stimulation amplitude. High intensities up to 8.5 V or 10.5 V were applied for chronic ALIC DBS across all trials with the exception of the most recent investigation [170], and the patient that declined between 4-12 months [179] had a lower stimulation intensity (2-4 V). A case series showed a ceiling effect of clinical response at six months which coincided with optimization of stimulation [180].…”
Section: Ocd Alic Targetmentioning
confidence: 99%
“…ALIC DBS responses appeared to rely on programming adjustments, particularly stimulation amplitude. High intensities up to 8.5 V or 10.5 V were applied for chronic ALIC DBS across all trials with the exception of the most recent investigation [170], and the patient that declined between 4-12 months [179] had a lower stimulation intensity (2-4 V). A case series showed a ceiling effect of clinical response at six months which coincided with optimization of stimulation [180].…”
Section: Ocd Alic Targetmentioning
confidence: 99%
“…Moreover, deficits in this cognitive domain have been associated with ordering and symmetry symptoms manifested by youth with OCD [62]. Since treatment response has been shown to improve the deficits in processing speed among both pediatric [63] and adult patients [64,65] with OCD, it could be hypothesized that impairments in this cognitive domain represent a modifiable vulnerability marker for OCD across the lifetime. In this sense, a study reported that pathological uncertainty in adult OCD patients underlies deficits in processing speed [66], which suggests that behavioral interventions could improve processing speed skills and consequently benefit children and adolescents at higher risk for the disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the tolerability and efficacy of DBS have been shown in a growing number of studies, the total number of OCD patients treated with DBS worldwide is just around 250, and the average sample size of all studies has been reported to be five [18]. The cognitive effects of DBS in patients with OCD has been investigated even less (see Table 4) [1,7,8,12,21,22,24,26,29,31,32,40,47]. Generally, diverse brain targets have been used across studies and sample sizes were also limited, ranging between one and 24 patients.…”
Section: Introductionmentioning
confidence: 99%